Pembuatan Media Poster Sebagai Pencegahan Anemia pada Pekerja Wanita di Pabrik X - Restu Alfi Bihusna; Agatha Widiyawati (Politeknik Negeri Jember, 2020)
Anemia was vulnerable to be experienced by women in Indonesia, especially in female workers. therefore, the anemia experienced by them needs special concern. To minimize this case of was by doing the prevention of anemia. The purpose of this study was to make poster media as a prevention of anemia for female workers in factory X. This research was a type of R & D research namely Research and Development that used the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The instruments used in this study were poll, PSP, informed consent and poster media. poll was used to determine the level of media poster feasibility. This study was conducted on January 21th, 2019. This development research used data analysis techniques, they were,Â qualitative descriptive and quantitative descriptive data analysis techniques. Qualitative data in the form of input and comments from the validator was used for media repair material that was going to be produced. Quantitative data were assessment score data from media validators, materials and factory female workers. The conclusion was that the validation of material experts was 100% with a very feasible category, and from media experts was 100% with a very feasible category. The test of acceptance of female workers was 95.8% with a very feasible category. Media Posters about anemia prevention could be said to be very feasible andÂ be applied toward factory female workers because the images and colors on the media poster were interesting so information was easily delivered